"First class oysters" : progress and constgraints in genetic improvement of the Pacific oyster (Crassostrea gigas) - Boudry, Pierre (First International Shellfish Conference, 2007)
The most significant genetic improvement for the production of Pacific oyster (Crassostrea gigas) up until now has been obtained through the production of triploids, particularly since the development of tetraploids in the mid 90s. Alternatively, quantitative genetics studies suggest that significant gains could be obtained in traits of aquacultural interest. However, the limited extent of hatchery propagation (compared with natural recruitment) in some countries and/or technical difficulties and biological characteristics of this species have retarded the development of selective breeding programs for C. gigas. Individual selection can however be performed easily in such a highly fecund species, though it often leads to small effective population sizes due to high variance in reproductive success and subsequently to inbreeding. Family-based selective breeding programs have been initiated in the U.S.A., Australia and New Zealand to improve growth, disease tolerance and yield. Despite recent progress in high density flow-through larval rearing systems, practical difficulties in breeding large numbers of families under homogeneous environmental conditions remain a major constraint for family-based selective breeding in oysters. Alternatively, multiplexed-microsatellite markers can be used to efficiently trace parentage and make mixed-family breeding a promising though challenging alternative. In Europe, no large scale selective breeding programs have yet been established in C. gigas but special attention has been paid to summer mortality. Studies have shown that family-based selective breeding can improve spat survival with no impact on growth. However, a genetic trade-off between survival and reproductive allocation was shown but it is influenced by environmental conditions. Such flexible relationships might explain how additive genetic variance for fitness-related traits is maintained in the wild and also why natural selection might not always work in favour of oyster farmers. QTL mapping and gene expression studies are now underway to further our understanding of C. gigas genetics and physiology, contributing to the selective breeding of "first class oysters".